Riccioli Revisited. A New Analysis of Giovanni Battista Riccioli’s New Almagest - Post, Anna-Luna (Incontri. Rivista europea di studi italiani, 2016)
Review of: Christopher M. Graney, Setting Aside All Authority. Giovanni Battista Riccioli and the Science against Copernicus in the Age of Galileo, University of Notre Dame Press, 2015, 270 p., ill., ISBN: 9780268029883, $29.00.